Management-related decision-making in midwifery management - Lenz, Iina (fi=Turun yliopisto|en=University of Turku|, 2018)
Managingdaily activities formanagersis a comprehensive collection of responsibilities that range from advocating the patients to ensuring the work safety of the employees. In recentresearch, decision-making and information needsofmanagers in nursing has been an increasing study focus. Yet, in midwifery there is no detailed, through the study of the topic yet.This is why the findings of this study are comparable and generalizable with other areas of specialities. The principal aim of the descriptive study was to identify midwifery manager’s decision-making during the management of their daily activities in maternity hospitals in Germany. In addition, the study focused on the information needs of midwifery managers. The main findings of the study can be both taken advantage of the orientation in midwifery manager’s job and of the educational leadership. The data was collected using a think-aloud method in natural setting. The data was analysed by using inductive content analysis method, because it enables the most truthful presentation of the findings. The study was conducted with Research-ethical legislation, and the trustworthiness of the study is taken into account, among other concerns, by centralizing the focus on study sample, think-aloud as a data collection method and diverse managers’ framework. Sampling of this study included four (n=4) voluntary managers of midwifery with at least two years of work experience in midwifery management. The data collection yielded sixteen hours of observational data, from which 271 decisions were identified. These were assembled into following categories: human resource and managers’personal performance management, management of the department’s performance, financial and materials management and management of stakeholder cooperation. Additionally, nine information need categories were constructed from a total of 180 information needs. Among other, these included a various number of statistics and programmes, up-to-date information, co-operations and alignments system. The role as a midwifery manager is challenging due to being a middle level management, but it offers multiple possibilities to influence the midwifery practice and its development. According to the results, management related decisions cover a diverse range of midwifery managers’ areas of responsibilities. The most time consuming area of decisions concerns the management of staffing levels. This is challenging in politically strained situations, like staff shortages. Keeping managers themselves and others constantly up-to-date is one of the many crucial, every-day activities of themanagers. In addition, the information needs to support the theory that decision-making ispre-eminent in multiprofessionalco-operation.Due to the small number of participants, the results are not generalizable. Nevertheless it is important to get more information about the specific topic to conclude if these findings differ from the other areas of specialities. Additional results can be used to develop a tool to support midwifery managers in decision-making and to provide access to larger sources of information on the subject.